Integrating Technology in PE: A Scoping Review of Drone Soccer as a Catalyst for Student Skill Development and Ethical Awareness - Frankie U Kei Wong; QiTing Zhou; Water Soi Po Wong (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study investigates drone soccer's potential as a pedagogical tool for integrating technology within physical education (PE). It bridges traditional athletics and STEM-oriented motor skills, exploring how this sport facilitates the dual-track development of technical proficiency and ethical responsibility in K-12 and higher education. Methodology: Guided by the updated PRISMA guidelines, this scoping review comprehensively synthesizes 35 key studies from multidisciplinary databases. It utilizes the I-TPACK and SAMR models to assess the depth of technology integration. Furthermore, reflexive thematic analysis (RTA) evaluates drone soccer's pedagogical and ethical efficacy across psychomotor, cognitive, and social-emotional domains. Main Findings: The analysis suggests that drone soccer functions as a significant catalyst for enhancing visual-motor integration (VMI), fine motor dexterity, and collaborative problem-solving. Beyond physical benefits, the sport provides a structured environment for instilling